Mancozeb induces nephrotoxicity by impairing the oxidative phosphorylation pathway: A transcriptome study - Yan Zhang; Ran Wen; Jialu Bao; Yinglan Gong; Xiaodan Wang (Ecotoxicology and Environmental Safety, 2023)
This study analyzed the mechanism underlying mancozeb (MCZ)-induced kidney injury by detecting kidney function indicators, combined with transcriptome and metabolome sequencing. Twenty mice were randomly assigned into two groups (control and MCZ groups) to explore the MCZ-induced kidney toxicity. The control group was gavaged with 0.2 mL of deionized water, and the MCZ group with 0.2 mL of 100 mg/kg MCZ for 30 days. The kidney structure of the MCZ group was damaged, with slight hyaline degeneration in the kidney tubular epithelial envelope. The creatinine (CRE) and uric acid (UA) were significantly increased in the MCZ group than in the control group. Moreover, the reactive oxygen species (ROS) significantly accumulated in the MCZ group kidneys. Compared to the control group, superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) were significantly decreased in the MCZ group, while the MDA content was substantially increased. The differentially expressed genes (DEGs) in the MCZ group were mainly enriched in the oxidative phosphorylation pathway. Besides, in the MCZ group, ndufs1 and ndufab1 genes were significantly up-regulated, while cox5b, ndufa5, and ndufa6 genes were significantly down-regulated, consistent with the PCR verification results. The metabolomic analysis identified cGMP-PKG signaling pathway of MCZ-induced nephrotoxicity, with Guanosine monophosphate and Adenosine 5′-monophosphate as the main altered metabolites. These results indicated that MCZ impairs the mice kidneys by obstructing the oxidative phosphorylation pathway, which increases oxidative stress in the kidneys, resulting in kidney injury.